Methodology to design a Map of Alert for population and housing censuses: the Portuguese case - Reis, E.; Vicente, P.; Rosa, A.; Marques, C. (Methodological Innovations, 2017)
The Portuguese Population and Housing Census is carried out every 10 years by Statistics Portugal. In the Census 2011, a new tool was developed to assist the Quality Assurance system in order to make the monitoring of fieldwork operations more efficient and thus diminish the uncertainties that could cause coverage error in the results. This tool, named as Map of Alert, presents a three-level typology of alert that ensures advance knowledge of the potential risk of each freguesia’s failure to meet the quality standards defined for the enumeration process. This article describes the methodological process that guided the development of the Map of Alert and presents the Map itself.